Treatment of post‐traumatic stress disorder in people with dementia: a structured literature review. Issue 3 (17th March 2023) - Ruisch, J.E.; Nederstigt, A.H.M.; van der Vorst, A.; Boersma, S.N.; Vink, M.T.; Hoeboer, C.M.; Olff, M.; Sobczak, S.
Abstract : Post‐traumatic stress disorder (PTSD) is associated with cognitive dysfunctions and is an independent risk factor for dementia. A recent study has found the prevalence of PTSD in people with dementia is 4.7%–7.8%. However, little is known about the effectiveness of PTSD treatment for people with dementia. The primary aim of the current study is to review previous studies on the treatment of PTSD in people with dementia. A structured literature review was performed using a 'Preferred Reporting Items for Systematic Reviews and Meta‐Analyses' analysis in PubMed, Embase, PsycINFO and CINAHL. Two independent researchers screened titles and abstracts. The inclusion criteria were: PTSD symptoms present, diagnosis of dementia, PTSD treatment form described and effects of the treatment mentioned. Articles that matched these criteria were included and content and quality were analyzed. We included nine articles, all case reports, with a total of 11 cases. The discussed treatment options are eye movement desensitisation and reprocessing (EMDR) ( n = 3), prolonged exposure ( n = 1), cognitive behavioural therapy ( n = 1) and pharmacological treatment ( n = 4). All articles reported a positive effect of the intervention on several monitored symptoms. Evidence for positive effects and feasibility of EMDR were most reliable, and it was applied in two articles of sufficient quality published in 2018 and 2019. EMDR 'on‐the‐spot' was described with positive effect in one article in which three cases were discussed. The quality of included papers ranged from insufficient to sufficient. This review shows that people with PTSD and dementia can benefit from PTSD treatment. EMDR, prolonged exposure, acceptance and commitment therapy and pharmacological treatment are applicable in this population. EMDR treatment is most described in this population ( n = 5) and shows positive results, and the studies are of sufficient quality ( n = 3). Further research in the form of a randomised controlled trial is required to study the effectivity of different treatment interventions in this population.